Pengaruh Kualitas Laporan Keuangan, Lama Jabatan Kepala Daerah dan Ukuran Pemerintah Daerah terhadap Transparansi Pemerintah Daerah - Wijita Lutvitasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study was conducted to determine whether there is an influence of the quality of financial reports, the length of office of the regional head and the size of the regional government on the transparency of the regional government through. The sampling technique used purposive sampling consisting of all regional governments in Indonesia in 2023 with a sample size of 517 regional governments. Based on the statistical tests that have been carried out, the results of this study indicate that the quality of financial reports and the size of the regional government have an effect on the transparency of the regional government through the website. Meanwhile, the length of office of the regional head does not affect the transparency of the regional government through the website.